Room-Temperature Palladium-Catalyzed Direct 2-Arylation of Benzoxazoles with Aryl and Heteroaryl Bromides() - Gao, Feng (2014)
An efficient room-temperature palladium-catalyzed direct 2-arylation of benzoxazoles with aryl bromides is presented. The Pd(OAc)(2)/NiXantphos-based catalyst enables the introduction of various aryl and heteroaryl groups, via a deprotonative cross-coupling process (DCCP) in good to excellent yields (75–99%).